Privacy and Security in Smartphones: Usability Barriers, Behavioral Nudges, and Compliance with the LGPD - Carneiro, Vitor Felipe B. A.; Belo, Felipe Fonteles; Araujo, Nelcileno Virgilio de S. (Anais do Congresso Latino-Americano de Software Livre e Tecnologias Abertas (Latinoware); 2025: Anais do XXII Congresso Latino-Americano de Software Livre e Tecnologias AbertasDO - 10.5753/latinoware.2025.16459, 2025)
The popularization of smartphones in Brazil increases users' exposure to cyber threats due to the accumulation of sensitive data on these devices. This article analyzes the usability challenges of native privacy and security settings on Android and iOS, especially for lay users. The research provides a multidisciplinary theoretical review involving information security, Human-Computer Interaction and the LGPD. The tension between usability and security and the importance of user-centered design are highlighted. The principles of privacy by design and security by default are discussed. The study argues that simply providing security tools is not enough. It is essential that the user understands and correctly configures these options. The text highlights the need for more intuitive interfaces and greater digital awareness.